2021
DOI: 10.3390/healthcare9080926
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level, Motivators and Barriers of Blood Donation among Students at Qatar University

Abstract: In Qatar, one out of every ten patients admitted to the hospitals is in urgent need of a blood transfusion or blood products. The aims of this study are as follows: (1) to assess the level of awareness and knowledge about blood donation and (2) to identify the factors that contribute to the willingness to donate blood among young adults. A cross-sectional survey using a constructed questionnaire was conducted among students at Qatar University. A total of 590 responses were collected, out of which 423 were sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
8
11
6
1
Order By: Relevance
“…On the motivation factors, similar findings were identified in donating to help others, and family or friends or relatives who are donors influenced them in this study and the Qatar study. 17 NGOs working for blood donation contacting them (40%) in this study differed from 7.6% of the Indian study in 2021 and when someone they know is in need (17.9%) which was contrasted with 66.7% of the Qatar study. 13,17 The standalone blood bank was the preferred choice of place to donate blood among this study's donors; this differed from the hospital-based blood bank of the international study in 2021.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…On the motivation factors, similar findings were identified in donating to help others, and family or friends or relatives who are donors influenced them in this study and the Qatar study. 17 NGOs working for blood donation contacting them (40%) in this study differed from 7.6% of the Indian study in 2021 and when someone they know is in need (17.9%) which was contrasted with 66.7% of the Qatar study. 13,17 The standalone blood bank was the preferred choice of place to donate blood among this study's donors; this differed from the hospital-based blood bank of the international study in 2021.…”
Section: Discussioncontrasting
confidence: 70%
“…17 NGOs working for blood donation contacting them (40%) in this study differed from 7.6% of the Indian study in 2021 and when someone they know is in need (17.9%) which was contrasted with 66.7% of the Qatar study. 13,17 The standalone blood bank was the preferred choice of place to donate blood among this study's donors; this differed from the hospital-based blood bank of the international study in 2021. 13 Among the 216 blood donors, their deterrents to blood donation were commonly restricted movements (77.3%), followed by fear of infection (67.6%), and being close to other donors (37.0%) and healthcare providers (33.3%).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Additionally, barriers are different between genders. Failing to meet the eligibility requirements has been reported commonly by females while most males reported that they were never asked to donate blood ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the studies concerning the status of knowledge on blood and marrow donation [1][2][3][4] . Secondly, the ones on communication, promotion, and motivation of potential and active blood donors to donate [5,6] together with the barriers involved [7,8]. Thirdly, the studies under preparation by various research centres, including Poland, on the personality domain [9].…”
Section: Introductionmentioning
confidence: 99%